Differential equation question

Watch
This discussion is closed.
Nylex
Badges: 10
Rep:
?
#1
Report Thread starter 16 years ago
#1
It's only a first order equation, but I'm stuck with the algebra.

The equation is: m(dv/dt) = mg - kv^2

=> (m/mg - kv^2)(dv/dt) = 1

=> (m/mg - kv^2) dv = dt

Integrating both sides gives: -(m/2kv)ln(mg - kv^2) = t + c

I want v(t), but the problem is the 2kv bit in the ln term. I can't see an easy way of re-arranging in terms of v :/. Have I done the integration wrong?
0
It'sPhil...
Badges: 2
Rep:
?
#2
Report 16 years ago
#2
(Original post by Nylex)
It's only a first order equation, but I'm stuck with the algebra.

The equation is: m(dv/dt) = mg - kv^2

=> (m/mg - kv^2)(dv/dt) = 1

=> (m/mg - kv^2) dv = dt

Integrating both sides gives: -(m/2kv)ln(mg - kv^2) = t + c

I want v(t), but the problem is the 2kv bit in the ln term. I can't see an easy way of re-arranging in terms of v :/. Have I done the integration wrong?
If you differentiate what you have it is not the same as the integrand. You cant use that method because the derivative of mg - kv^2 is -2kv and that is not present in the numerator of the integrand. It is possible to use a = v.dv/dx then use the fact that v = dx/dt
0
It'sPhil...
Badges: 2
Rep:
?
#3
Report 16 years ago
#3
Or to find v(t) you could try some variation of the v = tanhx substitution that takes into account the constants
0
elpaw
Badges: 15
Rep:
?
#4
Report 16 years ago
#4
m dv/dt = mg - kv²

terminal velocity, u, (when acceleration is 0): u = root(mg/k) (substitute this in for simplicity)

=> dv/dt = g [1 - (v/u)²]

using substitution z = v/u: (for simplicity)

=> INT [u / (1-z²)] dz = g INT [1] dt

=> 1/2 ln [(1+z)/(1-z)] = -1/2 ln[(1-z)/(1+z)] = gt/u + C
(the change of sign because it is easier to work with e^-t than it is to work with e^t)

=> [(1-z)/(1+z)] = Ae^[-(2gt/u)] = F(t) for simplicity

at t=0, v=0 => z = 0; => A = 1

=> z = (1-F(t))/(1+F(t))

=> v = u [1-e^(-2gt/u)]/[1+e^(-2gt/u)]

if you want to, you can substitute u back in:

v = root(mg/k) [1-e^(-2 root(gk/m) t)]/[1+e^(-2 root(gk/m) t)]
0
Nylex
Badges: 10
Rep:
?
#5
Report Thread starter 16 years ago
#5
Ah ****, thanx both of you.
0
X
new posts
Back
to top
Latest
My Feed

See more of what you like on
The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

Personalise

Should the rest of the UK follow the Scottish Results changes announced?

Yes they should (211)
60.11%
No they should not (102)
29.06%
Abstain (38)
10.83%

Watched Threads

View All
Latest
My Feed